Staphylococcus aureus nasal carriage – Interplay between host, microbe and the environment - Olsen, Karina (UiT Norges arktiske universitet, 2013)
Paper 2 of this thesis is not available in Munin: 2. Olsen K, Danielsen K, Wilsgaard T, Sangvik M, Sollid JUE, Thune I, Eggen AE, Simonsen GS, Furberg A-S.: 'Obesity and Staphylococcus aureus nasal colonization among women and men in a general population' (manuscript) Background: S. aureus colonizes persistently 20–30% of the adult human population (S. aureus carriers), and can also cause serious infections. The main objectives of this thesis were to investigate whether the modifiable risk factors such as serum vitamin D levels and obesity, and environmental factors such as current smoking, being a healthcare worker and residing with children were associated with S. aureus nasal colonization and carriage in an adult general population. The Tromsø Staph and Skin Study is part of the sixth Tromsø Study (Tromsø 6) carried out from October 2007 to December 2008 in the municipality of Tromsø. Our study supports the view that there is a complex interplay between host-, microbial- , and environmental factors during colonization and carriage. The current study indicates an inverse dose-response association between serum vitamin D concentration and the odds of S. aureus nasal colonization and carriage in non-smoking men. We observed that obese young and premenopausal women had increased odds of S. aureus nasal colonization independent of pre-diabetes and diabetes. Work in healthcare services was associated with increased odds of S. aureus nasal carriage among women. Odds were even higher among women residing with children. Our study suggests that a synergism between work and household is of importance for the overall S. aureus carrier state in HCWs.